Strength of Concrete Filled Steel Tubular Columns - I, Ajith; S, Dhamodaran; .S, Malarvizhi; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
Composite columns of steel and concrete have been used and studied world wide, but filled tubular columns need more attention. This paper presents an experimental study on the behavior of short concrete filled steel tubular columns (CFT) axially loaded in compression to failure. A total of 28 specimens (16 were filled with concrete and 12 were kept hollow) with different cross-sections were tested to investigate the load capacity. The length-to-diameter ratios of these columns were between 4 and 9. Parameters for the tests were tube shape and diameter-to-thickness ratio. Some of the concrete filled columns had internal bracing of #3 deformed bars. The test results are compared with the theoretical results and previous studies. The results show that the confinement effect on concrete does play a role in increasing the compressive strengths to almost 60% in some cases. Based on the test results, an equation to estimate the ultimate axial compressive loading capacities is also proposed for square CFT columns.